Tailoring choice between colonoscopy versus sigmoidoscopy for population-based colorectal cancer screening in Chinese patients: a prospective colonoscopy study. (October 2016) - Huang, Jason L W; Chen, Ping; Yuan, Xiaoqin; Wu, Yunlin; Wang, Harry H X; Jiang, Johnny Y; Wong, Martin C S
Abstract: Background: The rising incidence and mortality of colorectal cancer (CRC) in China highlights the pressing need for population-based screening. Flexible sigmoidoscopy (FS) is becoming increasingly popular as a primary screening tool; and in many regions of China, colonoscopy capacity is limited. However, FS is preferred for patients with a low risk of advanced proximal neoplasia (APN; ie, higher numbers needed to screen [NNS], since the test predominantly examines the distal colon. Tailoring endoscopic screening based on the risk of APN is necessary, especially in resource-deprived regions. Since old age and female sex are two important CRC risk factors, we hypothesised that younger Chinese women aged 50–59 years had a significantly lower APN rate than did older Chinese men. Methods: In 2013–15, we recruited 5833 asymptomatic participants aged 50–75 years who were registered for CRC screening in a large hospital-based endoscopy unit in Shanghai, China. Those with poor bowel preparation and whose colonoscopy failed caecal intubation were excluded. All polyps were removed as deemed appropriate and examined by histopathologists who were masked to the patients' data. We used χ 2 test to compare APN among different age and gender groups. The respective NNS were evaluated. Institutional ethics board approval was obtained by the hospital while informed consent was sought before subject recruitment. Findings: For men, the prevalence of APN was 2·5% (31/1264, 95% CI 1·7–3·5) in those aged 50–59 years, 4·1% (30/735, 2·9–5·8) in those aged 60–64 years, and 5·2% (38/727, 3·8–7·1) in those aged 65–75 years. In women, the APN prevalence was 0·7% (11/1607, 0·4–1·2) in those aged 50–59 years, 0·8% (6/766, 0·3–1·8) in those aged 60–64 years, 4·8% (35/734, 3·4–6·6) in those aged 65–75 years in those aged 66 years or older (p<0·001). The NNS by colonoscopy to detect one APN was 124 (95% CI 80–270) women aged 50–59 years and 96 (57–310) women aged 60–64, compared with the significantly lower NNS in other age or gender subgroups (range 14–58; p<0·001). Interpretation: These findings supported the application of sigmoidoscopy for CRC screening among female individuals younger than 65 years, given their low risk of APN and high NNS. Colonoscopy could be favoured for Chinese individuals aged 65 years or older. The feasibility and cost-effectiveness of this simple, tailored screening strategy in different Chinese populations should be further examined. Funding: None.